What stops a saccade?. (19th April 2017) - Optican, Lance M.; Pretegiani, Elena
Abstract : Rapid movements to a target are ballistic; they usually do not last long enough for visual feedback about errors to influence them. Yet, the brain is not simply precomputing movement trajectory. Classical models of movement control involve a feedback loop that subtracts 'where we are now' from 'where we want to be'. That difference is an internal motor error. The feedback loop reduces this error until it reaches zero, stopping the movement. However, neurophysiological studies have shown that movements controlled by the cerebrum (e.g. arm and head movements) and those controlled by the brain stem (e.g. tongue and eye movements) are also controlled, in parallel, by the cerebellum. Thus, there may not be a single error control loop. We propose an alternative to feedback error control, wherein the cerebellum uses adaptive, velocity feedback, integral control to stop the movement on target. This article is part of the themed issue 'Movement suppression: brain mechanisms for stopping and stillness'.